2009
DOI: 10.1017/s0033291709991528
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of change in depression severity during treatment with antidepressants

Abstract: Background. Response and remission defined by cut-off values on the last observed depression severity score are commonly used as outcome criteria in clinical trials, but ignore the time course of symptomatic change and may lead to inefficient analyses. We explore alternative categorization of outcome by naturally occurring trajectories of symptom change.Method. Growth mixture models were applied to repeated measurements of depression severity in 807 participants with major depression treated for 12 weeks with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
125
2
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(139 citation statements)
references
References 36 publications
(68 reference statements)
10
125
2
2
Order By: Relevance
“…48 25 weeks, is entirely consistent with the model reported in the large GENDEP sample of 807 patients with major depressive disorder treated with escitalopram or nortriptyline. 154 Also in line with the published literature, baseline severity of depressive symptoms predicted greater response to ADM. 155 Treatment with SSRIs also led to better outcomes over 25 weeks than treatment with other antidepressants. This supports previous reviews suggesting better practical outcomes for SSRIs are due to much better completion of therapeutic courses for SSRIs compared with other antidepressants like TCAs.…”
Section: Strengths and Limitations Of Folatedsupporting
confidence: 80%
“…48 25 weeks, is entirely consistent with the model reported in the large GENDEP sample of 807 patients with major depressive disorder treated with escitalopram or nortriptyline. 154 Also in line with the published literature, baseline severity of depressive symptoms predicted greater response to ADM. 155 Treatment with SSRIs also led to better outcomes over 25 weeks than treatment with other antidepressants. This supports previous reviews suggesting better practical outcomes for SSRIs are due to much better completion of therapeutic courses for SSRIs compared with other antidepressants like TCAs.…”
Section: Strengths and Limitations Of Folatedsupporting
confidence: 80%
“…Because quadratic growth terms were not significant for any class models, the best final solution was represented by the linear model (see Table 3). Following Uher et al (2010), and because the four trajectory solution presented one class with a very low proportion of subjects (27 subjects ¼ 4% of the sample), we found that the three trajectory solution provided the most interpretable description of prosocial development. This solution presented an adequate classification quality, as Table 2 Descriptive statistics and correlations among prosocial behavior, family dynamics and civic outcomes.…”
Section: Latent Class Growth Analysis For Prosocial Behaviors Datamentioning
confidence: 86%
“…[20] Despite the use of similar techniques, the number of identified course groups varied (2)(3)(4)(5). This could be explained by differences in numbers of follow-ups (7 [14] to 24 [20]), interval lengths (1 week [18] to 3 months [14]), and instruments. Interestingly, a short-term week-to-week perspective led to two to three classes, [17,18] whereas more widely spaced time frames resulted in four to six classes.…”
Section: Introductionmentioning
confidence: 99%
“…This could be explained by differences in numbers of follow-ups (7 [14] to 24 [20]), interval lengths (1 week [18] to 3 months [14]), and instruments. Interestingly, a short-term week-to-week perspective led to two to three classes, [17,18] whereas more widely spaced time frames resulted in four to six classes. [14,20] Although insightful, the inconsistent results so far make it hard to form a coherent view of typical course trajectories in clinical practice.…”
Section: Introductionmentioning
confidence: 99%